Concussion competencies: a training model for school-based concussion management - Arthur Maerlender; Jonathan D Lichtenstein; Jennifer Parent-Nichols; Kate Higgins; Peggy Reisher (Concussion, 2019)
This study reports on the use of ten knowledge competencies related to the behavioral management of concussion in schools. Trainings using these competencies as learning objectives were delivered t...